2006
DOI: 10.1007/s00467-006-0147-x
|View full text |Cite
|
Sign up to set email alerts
|

Vesicoureteral reflux increases the risk of renal scars: a study of unilateral reflux

Abstract: The aim of this study was to assess the impact of vesicoureteral reflux (VUR) on renal scar following acute pyelonephritis by comparing the refluxing renal units with nonrefluxing renal units in children with unilateral primary VUR. Forty-eight children with unilateral primary VUR diagnosed after the first pyelonephritis were enrolled. Mean age of patients was 1.0+/-1.6 years (29 boys and 19 girls). All patients underwent renal ultrasonography and renal 99 m-technetium dimercaptosuccinic acid (DMSA) scan withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 33 publications
4
25
1
5
Order By: Relevance
“…On the other hand, renal scar rate in non-refluxing renal units at presentation in this group of children (7/64, 11%) was significantly lower than the scar rate in refluxing renal units (80/212, 38%, P=0.000). A similar finding has been reported previously by Lee et al in children with unilateral reflux [25].…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, renal scar rate in non-refluxing renal units at presentation in this group of children (7/64, 11%) was significantly lower than the scar rate in refluxing renal units (80/212, 38%, P=0.000). A similar finding has been reported previously by Lee et al in children with unilateral reflux [25].…”
Section: Discussionsupporting
confidence: 80%
“…However, an association between urinary tract infection in children with vesicoureteral reflux and renal scarring remains unquestionable (Faust et al, 2009;Jahnukainen et al, 2005;Muinuddin et al, 2008). This was confirmed by recent studies that demonstrated an increase in the risk of renal scarring after acute pyelonephritis in patients with vesicoureteral reflux (Kanellopoulos et al, 2006;Lee et al, 2006;Polito et al, 2006;Oh et al, 2008). Studies by Svensson et al (2005) and Mohanan et al (2008) disclosed that renal scarring was detected less frequently in infants with vesicoureteral reflux and without urinary tract infection than in those with vesicoureteral reflux and urinary tract infection.…”
Section: Reflux Nephropathysupporting
confidence: 54%
“…The most concerning issue in an infant or child with UTI is the probability of underlying genitourinary anomalies and vesicoureteral reflux (VUR), which is frequently associated with renal scarring and eventually end-stage renal disease [1][2][3][4]. Therefore, the American Academy of Pediatrics recommends a voiding cystourethrography (VCUG) or radionuclide cystography at the earliest convenient time for children presenting with UTI [5].…”
Section: Introductionmentioning
confidence: 99%